2017
DOI: 10.1111/jam.13485
|View full text |Cite
|
Sign up to set email alerts
|

The effect of low-temperature laundering and detergents on the survival ofEscherichia coliandStaphylococcus aureuson textiles used in healthcare uniforms

Abstract: National Health Service (NHS) nurses are required to domestically launder their uniforms at 60°C to ensure safe removal of micro-organisms, 33% of NHS staff questioned said they launder their uniforms at 40°C, which could potentially result in transmission of hospital-acquired infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 14 publications
2
35
0
Order By: Relevance
“…; Riley et al . ). Likewise, the formation of biofilms may be supported if machines are used only rarely or mainly at low temperatures (Bloomfield et al .…”
Section: Discussionmentioning
confidence: 97%
“…; Riley et al . ). Likewise, the formation of biofilms may be supported if machines are used only rarely or mainly at low temperatures (Bloomfield et al .…”
Section: Discussionmentioning
confidence: 97%
“…However, the addition of silver additive to the rinse phase added value over that of biological detergent by significantly (P ≤ 0Á05) increasing the removal of S. aureus clinical isolate and E. coli type and clinical isolates (Table 5). Riley et al (2017) also reported that S. aureus was more susceptible to biological detergent than E. coli in solution at 40°C for 15 min; S. aureus was reduced by 3Á75 log 10 CFU while E. coli was not significantly reduced (7Á68 log 10 CFU survival). In this study, both S. aureus and E. coli were reduced to a greater extent in a 40°C wash with biological detergent than reported by Riley et al (2017), where approximately three log 10 CFU E. coli and S. aureus were removed and deposited onto sterile polycotton under clean conditions.…”
Section: Discussionmentioning
confidence: 91%
“…Riley et al (2017) also reported that S. aureus was more susceptible to biological detergent than E. coli in solution at 40°C for 15 min; S. aureus was reduced by 3Á75 log 10 CFU while E. coli was not significantly reduced (7Á68 log 10 CFU survival). In this study, both S. aureus and E. coli were reduced to a greater extent in a 40°C wash with biological detergent than reported by Riley et al (2017), where approximately three log 10 CFU E. coli and S. aureus were removed and deposited onto sterile polycotton under clean conditions. The current study highlights the importance of cleaning in the removal of micro-organisms from textiles and indicates that biological detergent is useful for the decontamination of laundry.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Faecal coliforms also survive for 120 days on cotton and blended textile at 25 • C (>1.1 ×10 4 CFU/ml), while few coliforms (1.1 ×10 2 CFU/ml) survive on silk (Colclasure et al, 2015). The greater survival of microorganisms on cotton compared to polyester and silk can be partly attributed to the moisture content of the different fibres (Colclasure et al, 2015;Riley et al, 2017). Cotton absorbs moisture to a greater extent than synthetic materials such as polyester, which supports the enhanced survival of microorganisms on this fibre type (Riley et al, 2017).…”
Section: Contamination Of Healthcare Textilesmentioning
confidence: 99%